Ventricular arrhythmias in ischemic versus nonischemic chronic heart failure. Is the equal sign between arrhythmia mechanisms and treatment strategies applicable? - R. D. Kurbanov; T. A. Abdullaev (Евразийский Кардиологический Журнал, 2011)
This article is devoted to the pathomorphological reasons of arrhythmias at patients with chronic heart failure ischemic and non-ischemic aetiology. Also the short review of researches by efficiency of several groups antiarrythmic drugs, including allapynin, and implanted devices is presented. Authors conclude, that the sights concerning antiarrythmic therapy are not universal for patients with chronic heart failure of various aetiology, and implanted devices are most effective in improved prognosis.